The Impact of Social Media Platforms on Youth Civic and Political Engagement Among Senior High School Students in Zone 4, Division of Zambales - Lea C. Saldivar (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study aimed to explore the impact of social media on civic and political engagement among senior high school students in Zone 4 of the Schools Division of the Province of Zambales, Philippines. This study randomly selected 681 student-respondents and how social media affects their civic and political engagement. Results show that the majority from this study respondents were typically Female, 17 years old, mostly from Senior High School Academic Track, from low-income class family, with gadgets and highly engaged in using social media. Findings revealed that Facebook was the most commonly used social media platform among the Senior High School students. It also shows that respondents demonstrated a high level of awareness regarding the impact of social media platforms on youth civic and political engagement. Meanwhile, statistical analysis showed a significant difference in the perceived impact of social media platforms on political issues engagement when students were grouped according to sex, monthly family income, and extent of social media usage. Further, significant differences were also found in the perceived impact of social media platforms on overall youth engagement in terms of social media usage. Meanwhile, there is no significant difference observed in the perceived impact of social media platforms on social issues engagement when students were grouped according to sex, age, Senior High School track, household income, gadgets used, and social media usage. Results from this study showed significant difference in terms of students’ awareness of social media and political issues which influenced using social media platforms.